PEREMPUAN DALAM PERSFEKTIF ALQURANULKARIM DAN HADIS NABAWI - Rahima Sikumbang Sarmadi (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2022)
AbstrakThe more angerous issue issue of gender problems, never stop rain tubs, begin to rain gerimis, even until the deras, from the time to time, from primitive times to the milineal era, from jahiliyah to modern times, always update and actual.The problem of the people’s view of women where since the first time before Islam came, until today, women are still also in the cosmos, accredited with a variety of religious reasons, and the understanding of the wrong society of the faceits faceits will support how the weakness of this woman, including the problem of women’s leadership, should not be women working for home.The actual tradition of ideology, one of the factors that make the problem of women is never exhausted, even many intellectuals, religions who write about women from various perspectives. One of the journals that have been written by Rena Asyari, one of the shepherds and teachers of the community of Pen Bandung, discussing women’s problems, he discussed about the negative side and positive women in the alquran. As well as Taqiyuddin Zarkasyi discussed about gender issues in the Orientation of Islamic Studies in the IAIN SU 2000-2010 (now UIN SU) he explained what the alquran view of women.The writer in this case, discussing things that are almost the same, only ada differences from the authors of research, which is more focused on pada the meaning of women according to alquran and sunnah, and what women's trials according to the alquran and faceis where the pada discussions previously did not mention the thing, the author reveals more in depth of the difference of the word and his interpreter according to the various mutations of the mufassir both the interpretation of alquran or explanation of the face itself. Because in the alquran meaning of women is much said, but the meaning is different.This research is a Library Research, which is a more minute research weighs on a library book, both classic web or contemporary books. Therefore, the author began from seeking a verse and faceits faceits who talked about women, seeing the word meaning of women in the alquran faceits hadits related to women, researching the interpretation of ulamas through the work of predecessed and contemporary ulamas, refers him to the book of tafsir. Then the author gave opinion and opinion in this case.This article starts from the preliminary chapter, the word meanings of women in the alquranulkarim, the origin of the incidence of women, rights and obligations as well as the existence of women both inside and outside the house, a mistaken view of women. Then the author pulls a short conclusion. The righteousness of the woman and the man differs from the terms of fhisyk, responsibility, but equally in the large part of the rights and obligations as the beakhkluq of Allah Ta’ala and as hambaNya.The end of the dive, this article, certainly far from the perfect word, hopefully it is beneficial for its own writers and also readers as well as the general public.Keywords: Female, Female Extensive,